Carotenoid metabolism strengthens the link between feather coloration and individual quality - Ryan J. Weaver (Nature Portfolio, 2018)
Studies of honest signaling have found an inconsistent relationship between carotenoid coloration and individual quality. Here, Weaver et al. compare dietary and biochemically converted carotenoid coloration using meta-analyses and show that converted carotenoids drive relationships with quality measures.